Computational fluid dynamics study of flow behaviour inmembrane module with multiple filaments - Hussain, Sharmina (BRAC University, 2010)
Membrane separation technology has added a new dimension in modern separation technology. The recent novel development in membrane process have made it possible to use various different purposes at economical rates with additional flexibility and improved efficiencies. Feed spacers can provide higher shearrates at the membrane surface. As a result concentration polarization and membrane fouling can be reduced. The present work is devoted to investigate the hydrodynamics in two dimensional spacer filled channels. Three different configurations of the cylindrical spacers are investigated with different channel Reynolds number and different meshlength. Different size and shape of formation of recirculation region, upstream and downstream of the spacers are closely observed. This recirculation regions have an important role in enhancing the mass transfer in reattachment region.